Análise Multivariada Da Divergência Genética Em 29 Populações De Cubiu (Solanum Sessiliflorumdunal) Avaliada Na Zona Da Mata Do Estado De Pernambuco - Silva Filho, Danilo Fernandes da; Anunciação Filho, Clodoaldo José da; Noda, Hiroshi; Reis, Odemar Vicente dos (Acta Amazonica, 1995)
The amplitude of the genetic divergence among 29 populations of cubiu from the germplasm collection maintaned by the Amazonian National Research Institute (INPA) was evaluated. The trial was carried out in the Vitória de Santo Antão Experiment Station of the Pernambuco State Research Enterprise (IPA), Pernambuco, Brazil. The experimental design was a randomized complete block, with four replications. The following characters of agronomic importance were evaluated; fruit width (cm); fruit length (cm); stem diameter at soil level (cm); leaf area (cm2); plant height (cm); total fruit number/plant; average fruit weight/ plant (g); estimated fruit yield (Mt/ha); loculi number; pulp thickness (mm) and total soluble solids (%). Cluster analysis (Tocher Optimization Method, using the Mahalanobis Generalized Distance) grouped the 29 cubiu accessions into 9 groups. The accessions from Umariaçú (AM) and São Paulo de Olivença (AM) were most closely related, and are also geographically close, and those from Borba (AM) and São Gabriel da Cachoeira (AM) were most divergent, both genetically and geographically. The accessions from Atalaia do Norte (AM), Borba (AM), Iquitos (Peru), São Gabriel da Cachoeira (AM) and Belém (PA) presented good agronomic traits and were divergent among themselves. Their use as potential progenitors in the cubiu breeding program may provide both good quality and heterosis.
Multivariate Anaysis of the Genetic Divergence in 29 Populations of Cubiu (Solanum sessiliflorum) Evaluated in the Zona da Mata of the State of Pernambuco
Keywords: Orinoco Apple; Solanum Sessiliflorum; Solanaceae; Genetic Divergence; Breeding; Cubiu; Solatium Sessiliflorum; Solanaceae; Divergência Genética; Melhoramento